The Legal Implications of Values Education - Shaw, Brian (Maine Policy Review, 1992)
As Rushworth Kidder noted in another article in this issue, the mere mention of values education creates a stir among its advocates and detractors. Brian Shaw, a Portland attorney whose practice focuses in part on public school law, was asked by Maine Policy Review to address the legal issues involved in values education in public schools. The article includes an overview of those issues and, by way of illustration, a case study from a Maine school district.